Exploring Drivers of Edu-Tourist Satisfaction and Revisit Intention at Intangible Cultural Heritage Sites: Insights from Jiangxi, China - Hu, Peipei (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study aims to analyze the factors that influence edu-tourists’ satisfaction and revisit intention at intangible cultural heritage sites. It focuses on attitudes, subjective norms, perceived behavioral control, perceived service quality, and destination image, and explores how these factors interact to shape tourist behavior. Research design, data and methodology: A survey of 500 student-tourists from Nanchang Institute of Science and Technology was conducted using a quantitative research design. Data were collected through both online and offline questionnaires. The analysis employed JAMOVI and SPSS software, while confirmatory factor analysis (CFA) and structural equation modeling (SEM) were used to assess model fit, reliability, validity, and causal relationships among the constructs. Results: Findings reveal that attitudes, subjective norms, and perceived behavioral control significantly enhance satisfaction. In addition, perceived service quality and destination image positively contribute to tourists’ overall satisfaction. Satisfaction itself acts as a critical mediator, directly influencing revisit intention and highlighting its central role in behavioral decision-making. Conclusions: Both psychological factors and destination characteristics strongly affect edu-tourists’ satisfaction. These results contribute theoretically to the study of educational and cultural tourism and provide practical guidance for service innovation, destination management, and marketing strategies to foster tourist loyalty in intangible cultural heritage contexts.